Lithium chloride modulates macrophage polarization and enhances bone defect healing in the induced membrane technique by activation of Wnt/β-catenin signaling - Qi, Yong; Zhang, Wei; Zhang, Ran; Ou, Shuanji; Xu, Changpeng; Yang, Yang (Frontiers in Pharmacology, 2025)
BackgroundThe induced membrane technique (IMT) has become an effective method for treating bone defects; however, its efficacy is influenced by various factors. As an agonist of the Wnt/β-catenin cascade, lithium chloride (LiCl) has demonstrated notable osteogenic efficacy in recent years. Our current study systematically evaluated the therapeutic efficacy of LiCl in IMT-mediated bone reconstruction and the potential mechanisms by which it regulates macrophage polarization, osteoblast proliferation, and differentiation.MethodsForty-eight male Sprague-Dawley rats were randomly assigned to 3 separate groups: high-dose LiCl (H-LiCl), low-dose LiCl (L-LiCl), and control group. A femoral bone defect model was established, and a PMMA spacer was subsequently implanted into the defect site in the first stage. After induced membrane formation, autologous bone grafts were implanted in the second stage. After 12 weeks, bone defect healing was evaluated by X-ray, micro-CT, and histological detection. Enzyme-linked immunosorbent assay (ELISA) and Immunohistochemical staining were used to evaluate the inflammatory cytokines in the induced membranes (IMs). Meanwhile, co-culture system consisting of RAW264.7 cells and bone marrow-derived mesenchymal stem cells (BMSCs) was used to assess the effects of LiCl on cell proliferation, macrophage polarization, osteogenic differentiation, and the Wnt/β-catenin pathway in vitro.ResultsThe high-dose LiCl group showed significant improvements in bone density, bone volume/total volume (BV/TV), and trabecular structure, exhibiting better bone repair outcomes. In vitro, LiCl markedly induced M2 macrophage polarization and enhanced BMSCs proliferation and mineralization.ConclusionLiCl significantly improved bone regeneration and mineralization during bone defect repair by promoting M2 macrophage polarization, activating the Wnt/β-catenin pathway, and enhancing BMSCs differentiation.